Verification and Validation of a Four-Gene Panel as a Prognostic Indicator in Triple Negative Breast Cancer - Pariyar, Mamta; Thorne, Rick F.; Scott, Rodney J.; Avery-Kiejda, Kelly A. (Frontiers in Oncology, 2022)
Triple negative breast cancer (TNBC) is a highly aggressive subtype with a high rate of metastasis, early distant recurrence and resistance to therapy leading to worse survival than other breast cancer subtypes. There are no well-established biomarkers that can determine women who will do better and those who are likely to have poorer outcomes with TNBC, nor are there targeted therapies. Thus, the identification of prognostic and/or predictive biomarkers will enable tailored therapies based on their likelihood of disease outcomes and may prevent over- and under-diagnosis. Previous studies from our laboratory have identified four genes (ANP32E, DSC2, ANKRD30A and IL6ST/gp130) that are specific to TNBC and were associated with lymph node metastasis (LNmets), the earliest indicator of tumor progression via distal spread. This study aimed to validate these findings using absolute quantitation by digital droplet PCR (ddPCR) and to determine relationships with clinicopathological features and survival. Our analysis confirmed all four genes displayed significant expression differences between TNBC cases and non-TNBC cases. Moreover, low IL6ST expression was significantly associated with grade 3 disease, hormone receptor negativity and earlier age at diagnosis; low ANKRD30A expression was associated with tumor size; and high ANP32E expression was significantly associated with grade and the number of positive lymph nodes. Individually, three of the four genes were associated with relapse-free survival in TNBC and in combination, all four genes were significantly associated with TNBC survival, but not in hormone receptor-positive cases. Collectively our results suggest that the four genes may have utility in TNBC prognostication.